2008
DOI: 10.1111/j.1582-4934.2008.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins: essential proteins for apoptosis regulation

Abstract: Many different external and intrinsic apoptotic stimuli induce the accumulation in the cells of a set of proteins known as stress or heat shock proteins (HSPs). HSPs are conserved proteins present in both prokaryotes and eukaryotes. These proteins play an essential role as molecular chaperones by assisting the correct folding of nascent and stress-accumulated misfolded proteins, and by preventing their aggregation. HSPs have a protective function, that is they allow the cells to survive to otherwise lethal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
314
0
23

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(352 citation statements)
references
References 164 publications
(183 reference statements)
15
314
0
23
Order By: Relevance
“…37 Given the known biological properties of the identified proteins, differential expression of 11 of them might explain the effects of DN-STAT5A and HSP might represent one major link between DN-STAT5A and apoptosis. Various studies have highlighted the protective effects of HSP against apoptosis in response to various stimuli such as hyperthermia, oxidative stress or staurosporine 38 From this point of view, the decreased expression of Hsp27 and Hsp70 might provide some cues to explain the susceptibility of NALM6D5A cells to apoptosis. We believe that the Hsp27 effect is mediated by Daxx, a protein involved in Fas-mediated cell death 31 given the increased proportion of Daxx in the cell cytoplasm together with the downregulation of Hsp27 expression and phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…37 Given the known biological properties of the identified proteins, differential expression of 11 of them might explain the effects of DN-STAT5A and HSP might represent one major link between DN-STAT5A and apoptosis. Various studies have highlighted the protective effects of HSP against apoptosis in response to various stimuli such as hyperthermia, oxidative stress or staurosporine 38 From this point of view, the decreased expression of Hsp27 and Hsp70 might provide some cues to explain the susceptibility of NALM6D5A cells to apoptosis. We believe that the Hsp27 effect is mediated by Daxx, a protein involved in Fas-mediated cell death 31 given the increased proportion of Daxx in the cell cytoplasm together with the downregulation of Hsp27 expression and phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that the ATPase domain of HSP72 plays a key role in sequestering AIF in the cytosol, thereby inhibiting AIF nuclear translocation [38]. A potential additional mechanism that may contribute to increase the apoptosis resistance in TFK-1 cells is represented by the constitutive expression of pro-survival HSP27 [21,39,40]. This protein antagonizes BAX-mediated mitochondrial injury by inhibiting conformational activation of BAX thus reducing cytochrome c and AIF leakage and increasing significantly cell survival [37,41].…”
Section: Discussionmentioning
confidence: 99%
“…Among those proteins directly or indirectly linked to the BCL-2 protein family, the heat shock proteins (HSPs) play key roles in inhibiting the cell death pathway at multiple checkpoints [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recently published research [3] has revealed an unexpected role for an antiapoptotic heat shock protein (HSP) [4], Hsc71, in Cnidarian pattern formation. While our research also has implications for stem cell and cancer biology, this article focuses on the patterning aspect of our findings, which could have broader implications for human congenital defects (see original publication).…”
Section: Heat Shock Proteins Wnt Signalling and Patterningmentioning
confidence: 99%